Penerapan Metode Tanya Jawab Dalam Meningkatkan Pemahaman Teks Dengan Membaca Intensif dan Membaca Teks Drama - Nurlaili, Nurlaili (Komunitas Manajemen Kompetitif, 2017)
Abstract: Learning Indonesian m engenai understand the text into a relatively elusive subject, during the teachers use the lecture method and presumably through the use of question and answer method can be more effective in teaching. Through action research methods classes in primary schools and the data collected through tests and observation and analyzed with descriptive techniques. The obtained results of the study that the application of teaching methods debriefing in order to enhance students 'understanding of intensive reading and reading drama in the classroom texts on subjects Indonesian was able to increase the students' understanding. Keywords: Keywords: Question and Answer Methods, Understanding Students